Malaria Diagnosis through Conventional Methods: A Comprehensive Review - Ramesh Kumar; Dinesh Kumar; Rajni Tanwar; Amandeep Mor (International Journal of Pathogens, 2024)
The incidence of drug-resistant parasite strains is rising, there is an apparent increase in the number of cases of malaria worldwide, and in a small number of cases and there has been a dramatic rise in international migration and travel. Over 1 million people die from malaria every year; 90% of these deaths are in African children, who live in tropical and subtropical regions. Although there are now efficient techniques to treat malaria, the disease is nevertheless becoming more prevalent for a variety of reasons. The therapy and control of malaria in this emergency circumstance depends on quick and accurate diagnostic techniques. Accurate diagnosis is essential in guiding appropriate treatment and improving patient outcomes. In recent years, advancements in technology have led to the development of new diagnostic tools, including genetic testing and molecular imaging, which have improved the accuracy and efficiency of diagnosis. However, clinical diagnosis remains a complex and challenging process, requiring careful consideration of patient history, symptoms, and test results. This abstract highlight the Leishman stain, Gram stain, and field A and B stain.
Keywords: Diagnostic; Gram stain; Leishman stain; Malaria; parasite